The Model of the Efficiency Education Supervision of Phetchabun Primary Educational Service Area Office 2 - Namthongton, Anan; Jaichalad, Nongluck (Education journal Faculty of Education, Nakhon Sawan Rajabhat University, 2022)
The purposes of this research were 1To study The Model of the Efficiency Educational Supervision of Phetchabun Primary Educational Service Area Office 2 2) To make the Policy recommendation of the Efficiency Education Supervision of Phetchabun Primary Educational Service Area Office 2 The research methods of this research had 2 steps 1) The study The Model of the Efficiency Education Supervision of Phetchabun Primary Educational service Area Office 2 were 1.1) The synthesized the factors of the Model of the Efficiency Educational Supervision of Phetchabun Primary Educational Service Area Office 2 were used through the synthesis the content from the documents, theories and the findings of the previous research, 1.2) The Checking of the Model of Efficiency Education Supervision for Phetchabun Primary Educational Service Area Office 2 were used through Propriety and Feasibility checked from 9 experts, 2) The making the Policy of the recommendation of the Efficiency Educational Supervision of Phetchabun Primary Educational Service Area Office 2 The findings of this research were as follows; 1)To study The Model of the Efficiency Educational Supervision of Phetchabun Primary Educational Service Area Office 2 1.1 The synthesis of the factors of the Model of the Efficiency Educational Supervision of Phetchabun Primary Educational Service Area Office 2 had 5 factors, 1The purpose of Educational Supervision had 3 Items ,2) The principle of Educational Supervision had 4Items,3) The process of Educational Supervision (POLIAS) had15Items, 4) The framework of Educational Supervision had 5 Items, and 5)The factors of Educational Supervision success had 4 Items. 1.2 The Checking of the Model of the Efficiency Educational Supervision of Phetchabun Primary Educational Service Area Office 2 found that the expert had through Propriety and Feasibility 5factors were at high levels. The results of the Policy recommendation of the Efficiency Educational Supervision of Phetchabun Primary Educational Service Area Office 2 found that 6 factors were 1) The name of Policy recommendation 2) The purpose of Supervision ,3) The principle of Supervision, 4) The process of Supervision (POLIAS), 5) The framework of Supervision, and 6) The factors of the Supervision success.